Influence of Human–Computer Interaction-Based Intelligent Dancing Robot and Psychological Construct on Choreography - Yang, Liu (Frontiers in Neurorobotics, 2022)
In order to study the influence of Artificial Intelligence (AI) on dancing robots in choreography, this paper introduces the biped-humanoid robot-imagined choreography model alongside the Psychological Space Construction (Psychological Construct) and Human-Computer Interaction (HCI). The proposed model is based on deep learning and imitating human thinking and is capable of imagining new dance elements. Finally, simulation experiments are designed to verify the model's effectiveness. Dance professionals are invited to evaluate the robot-imagined dance posture. The results show that the proposed model can vividly imitate human dancers and imagine and create new dance movements. The average basic feature retention and innovation scores of 30 new dance elements imagined on the L1 (Head) are 7.29 and 7.64, respectively. By comparison, similar scores on 30 new elements in L2 (Upper-body) are 7.73 and 7.40, respectively. Therefore, the proposed intelligent robot-imagined choreography model can help the dancing robot choreograph more finely and improve the choreography efficiency. The research results have significant practical value for dance teaching. Key words: dance creation, Human-computer interaction, Artificial intelligence, Deep